Activity motor pattern and heart rate during elite team handball matches - Póvoas, S. C.; Soares, J. M.; Rebelo A. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
This study analyses time-motion and cardiovascular demands of top elite male Portuguese handball players during the match. Main results showed that handball is a high demanding intermittent sport despite the amount of time spent in low intensity activities, since high-intensity actions and moments are required throughout the game.